La investigación formativa, los semilleros estudiantiles y la capacidad sanitarista cotransformadora en la carrera de Medicina - García Pérez, Reinaldo Pablo (Mediciego, 2020)
When carrying out a critical analysis of the teaching of research in medical training in Cuba, Bayarre et al.(1) identified that, although it is considered among the three essential pillars, it has been neglected in the curriculum.